Identification of a Porcine Liver EomeshighT-betlow NK Cell Subset That Resembles Human Liver Resident NK Cells - De Pelsmaeker, Steffi; Denaeghel, Sofie; Hermans, Leen; Favoreel, Herman W. (Frontiers in Immunology, 2019)
Natural killer (NK) cells are cells of the innate immunity and play an important role in the defense against viral infections and cancer, but also contribute to shaping adaptive immune responses. Long-lived tissue-resident NK cells have been described in man and mouse, particularly in the liver, contributing to the idea that the functional palette of NK cells may be broader than originally thought, and may include memory-like responses and maintaining tissue homeostasis. Remarkably, liver resident (lr)NK cells in man and mouse show substantial species-specific differences, in particular reverse expression patterns of the T-box transcription factors Eomesodermin (Eomes) and T-bet (EomeshighT-betlow in man and vice versa in mouse). In pig, compared to blood NK cells which are CD3-CD8αhigh cells, the porcine liver contains an abundant additional CD3-CD8αdim NK cell subpopulation. In the current study, we show that this porcine CD3-CD8αdim liver NK population is highly similar to its human lrNK counterpart and therefore different from mouse lrNK cells. Like human lrNK cells, this porcine NK cell population shows an EomeshighT-betlow expression pattern. In addition, like its human counterpart, the porcine liver NK population is CD49e- and CXCR6+. Furthermore, the porcine EomeshighT-betlow liver NK cell population is able to produce IFN-γ upon IL-2/12/18 stimulation but lacks the ability to kill K562 or pseudorabies virus-infected target cells, although limited degranulation could be observed upon incubation with K562 cells or upon CD16 crosslinking. All together, these results show that porcine EomeshighT-betlow NK cells in the liver strongly resemble human lrNK cells, and therefore indicate that the pig may represent a unique model to study the function of these lrNK cells in health and disease.